Attack Intensity of Coffee Berry Borer Hypothenemus Hampei Ferr at Different Altitudes in Simalungun Regency and Control Efforts Using Attractants - Rosmaria Girsang; Mei Linda Sipayung; Warlinson Girsang; Meylida Nurrachmani; Tri Astuti; Surya Bambang Yudoyono; Ahmad Husin (Jurnal Penelitian Pendidikan IPA, 2023)
The research was carried out in people's coffee plantations at 4 locations at different altitudes in Simalungun Regency. The aim of the research was to determine the intensity of attacks by the coffee berry borer Hypothenemus hampei Ferr on land at different altitudes, and to determine the effectiveness of synthetic attractant traps to control it. The research method used a series design (randomized design series groups), which was carried out on coffee plantations at altitudes of 550, 850, 1,000 and 1,150 meters above sea level. At each plantation location, in an effort to control Hypothenemus hampei Ferr attacks, 3 (three) types of synthetic attractant traps were installed: Hypotan 500 SL, Koptan and Atrakop 500 L. The results of the research showed that the intensity of Hypothenemus hampei Ferr attacks tended to decrease in coffee plantation locations. higher above sea level and vice versa. The attractant types Hypotan 500 SL, Koptan and Atrakop 500 L showed no significant difference in effectiveness for trapping the coffee berry borer Hypothenemus hampei Ferr. However, these 3 types of attractants have not been able to reduce the intensity of attacks from puso, heavy and moderate categories to light attack categories.